Body Mass Index Greater Than 35 Is Associated With Increased Major and Radiographic Complications After Minimally Invasive Adult Spinal Deformity Surgery. (1st September 2019) - Than, Khoi D; Tran, Stacie; Chou, Dean; Fu, Kai-Ming G; Park, Paul; Fessler, Richard G; Wang, Michael Y; Kanter, Adam S; Okonkwo, David O; Nunley, Pierce D; Anand, Neel; Uribe, Juan S; et al.
Abstract: INTRODUCTION: As the obesity epidemic continues and the recognition of adult spinal deformity (ASD) increases, a growing number of obese patients are undergoing surgery to correct ASD. Minimally invasive techniques may be advantageous for obese patients to minimize blood loss. To date, the literature examining the impact of obesity on complications after minimally invasive ASD surgery has been scarce. METHODS: A multicenter database of ASD patients was reviewed. Patients who had at least 2 yr of follow-up were analyzed. Demographic, radiographic, clinical outcomes, and postoperative complications were assessed. A body mass index (BMI) threshold of 35 was selected to more accurately reflect real-world practices. RESULTS: A total of 220 patients were included: 196 had a BMI <35 and 24 had a BMI >35 (26.3 vs 38.4, P < .001). When comparing patients with a BMI threshold of 35, there was no difference in baseline age, levels instrumented, and most pre- and postoperative radiographic parameters and clinical outcomes. Patients with BMI >35 did have higher preopearative back pain than BMI <35 (visual analog scale 7.9 vs 6.8, P = .013) and postoperative Cobb angle (17.8 vs 12.6, P = .031). There was no difference between groups in overall complications, reoperations, infections, implant failures, surgical site infections, or minor, cardiopulmonary, gastrointestinal, and operative complications. Patients with BMI >35 had more major (45.8% vs 23.0%, P = .015) and radiographic (37.5% vs 19.9%, P = .049) complications than patients with BMI <35. Patients with BMI <35 had more neurological complications (17.3% vs 0%, P = .026). CONCLUSION: In this retrospective review of a large database of patients undergoing minimally invasive surgery for ASD, patients with BMI > 35 suffered from more major and radiographic complications but fewer neurological complications than patients with BMI <35.